KADAR AIR DAN BILANGAN ASAM DARI MINYAK KELAPA YANG DIBUAT DENGAN CARA TRADISIONAL DAN FERMENTASI - Dwi Adhi Suastuti, N. G. A. M. (Jurnal Kimia (Journal of Chemistry), 2012)
The water contents and acid numbers of coconut oils made by thad way and by fermentation were compared. The water contents were determined using oven method while the acid numbers was cletermined by titration. Both parameters were compared on oils exposed to open air for 0, 1, 2, 3, and 4 weeks. Result showed that water contents and acid value of coconut oils produced by fermentation process were higher than coconut oils made by traditional ways. Water content of coconut oil made by traditional way and by fermentation were elevated during exposure. The highest water content of both coconut oils made by traditional way and fermentation process after 4 weeks exposure were 0,03 % and 0,06 % respectively, while the highest acid numbers of both coconut oils products after 4 weeks exposure were 0,75 and 0,89 mg KOH/g respectively
Keywords: Water content, Acid Value, Traditional Coconut Oil, Fermentation Coconut oil